2011
DOI: 10.1007/s00213-011-2589-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable role of tumor necrosis factor alpha gene deletion in methamphetamine self-administration and cue-induced relapsing behavior in mice

Abstract: TNF-α affects METH self-administration and motivation to self-administer METH but contributes to neither METH-associated cue-induced relapsing behavior nor food reward and food-seeking behavior. TNF-α may be explored for use as a diagnostic biomarker for the early stage of drug addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…It was reported that the levels of circulating TNF-α have been altered in alcoholics, cocaine abusers and opiate addicts. In addition, it has been suggested that TNF-α can be a potential diagnostic biomarker for drugs of abuse [ 60 , 61 , 62 , 63 , 64 , 65 ]. In an animal model, TNF-α has been investigated as a potential therapeutic target to prevent drug abuse and to increase the chance of cessation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the levels of circulating TNF-α have been altered in alcoholics, cocaine abusers and opiate addicts. In addition, it has been suggested that TNF-α can be a potential diagnostic biomarker for drugs of abuse [ 60 , 61 , 62 , 63 , 64 , 65 ]. In an animal model, TNF-α has been investigated as a potential therapeutic target to prevent drug abuse and to increase the chance of cessation.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model, TNF-α has been investigated as a potential therapeutic target to prevent drug abuse and to increase the chance of cessation. [ 61 ]. The current findings of the association of low TNF-α with food addiction is very interesting and unique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these findings, mice treated with methamphetamine show brain region-specific increases in the expression of proinflammatory cytokines (e.g., IL-1β) up to 3 weeks after methamphetamine exposure (Loftis et al, 2011). In a rigorous study designed to evaluate whether or not deletion of the TNF-α gene in mice affects addictive-like behavior, including methamphetamine self-administration, motivation to self-administer methamphetamine, and cue-induced reinstatement of methamphetamine-seeking behavior, Yan, Nitta, Koseki, Yamada, and Nabeshima (2012) measured methamphetamine self-administration and reinstatement of drug-seeking behavior in TNF-α knock-out and wild-type mice. The authors observed an upward shift of dose responses to methamphetamine self-administration under a fixed ratio schedule of reinforcement in the TNF-α knockout as compared with wild-type mice, indicating that mice lacking TNF-α administered more methamphetamine than controls.…”
Section: Partmentioning
confidence: 99%
“…Taken together, these findings demonstrate that TNF-α signaling affects methamphetamine self-administration and motivation to obtain the drug. However, TNF-α did not appear to contribute to methamphetamine-associated cue-induced relapsing behavior (Yan et al, 2012). …”
Section: Partmentioning
confidence: 99%